Radiopaque microsphere-hydrogel composite for extended-release intratumoral immunotherapy in a large animal model - Anup Kumar Patel; Imran Shair Mohammad; Marcin Kortylewski; Steven T Rosen; Jonathan Kessler; Julie Ressler; Cherng H Chao; Taedo Jake Choi; Chandana Lall; Catalina Guerra; F. Edward Boas (Drug Delivery and Translational Research, 2026)
Intratumoral injection of immune stimulants could potentially reverse the immunosuppressive tumor microenvironment, but the injected drug rapidly washes out into the systemic circulation. This results in systemic toxicity, and reduced efficacy, potentially requiring daily injections to generate an antitumor immune response. To address this problem, we developed an extended-release hydrogel that retains the immunotherapy agent at the injection site, and releases it over several days, even in highly vascular liver tumors. The extended-release hydrogel is a composite material containing drug-loaded microspheres (for sustained, tunable drug release), embedded in a radiopaque cross-linked hydrogel (for local retention). Using these new intratumoral drug carriers, we demonstrate the ability to safely deliver a wide range of different immunotherapy agents (cytokines, oligonucleotides, small molecules) into pig liver tumors, with no acute systemic toxicity. The microsphere gel reduces burst release by 7.8x (compared to microspheres), and increases half-life by > 15x (compared to hydrogel). Thus, the immunotherapy-loaded microsphere gel enables sustained intratumoral delivery of immune stimulants from a single injection, with low systemic toxicity.

Age of the Acraman impact ejecta layer in the adelaide superbasin and Implications on clay-mineral provenance from the Rb–Sr systematics of middle Ediacaran shales - Alan S. Collins; Morgan L. Blades; Darwinaji Subarkah; Holly Cooke; Lesley Edwards; Chelsea Forbister; Jake Jolly; Jarred C. Lloyd; Sarah E. Gilbert; Stefan Löhr; Juraj Farkaš; Victor Gostin (Precambrian Research, 2026)

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

Existing dataset suggests lakes in agricultural watersheds are warming faster than urban or forested lakes - Patrick T. Kelly; Kathleen Cutting; Samantha Supan; Jake Ackerman; Rebecca Erickson; Edward Pope (Aquatic Sciences, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Quantification of age-related changes in the structure and mechanical function of skin with multiscale imaging - Alan E. Woessner; Nathan J. Witt; Jake D. Jones; Edward A. Sander; Kyle P. Quinn (GeroScience, 2024)
The mechanical properties of skin change during aging but the relationships between structure and mechanical function remain poorly understood. Previous work has shown that young skin exhibits a substantial decrease in tissue volume, a large macro-scale Poisson’s ratio, and an increase in micro-scale collagen fiber alignment during mechanical stretch. In this study, label-free multiphoton microscopy was used to quantify how the microstructure and fiber kinematics of aged mouse skin affect its mechanical function. In an unloaded state, aged skin was found to have less collagen alignment and more non-enzymatic collagen fiber crosslinks. Skin samples were then loaded in uniaxial tension and aged skin exhibited a lower mechanical stiffness compared to young skin. Aged tissue also demonstrated less volume reduction and a lower macro-scale Poisson’s ratio at 10% uniaxial strain, but not at 20% strain. The magnitude of 3D fiber realignment in the direction of loading was not different between age groups, and the amount of realignment in young and aged skin was less than expected based on theoretical fiber kinematics affine to the local deformation. These findings provide key insights on how the collagen fiber microstructure changes with age, and how those changes affect the mechanical function of skin, findings which may help guide wound healing or anti-aging treatments.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

The methodology and results of using life cycle assessment to measure and reduce the greenhouse gas emissions footprint of “Major Events” at the University of Arizona - Leah Edwards; Jake Knight; Robert Handler; Joseph Abraham; Paul Blowers (The International Journal of Life Cycle Assessment, 2016)

Tupinambis merianae as nest predators of crocodilians and turtles in Florida, USA - Frank J. Mazzotti; Michelle McEachern; Mike Rochford; Robert N. Reed; Jennifer Ketterlin Eckles; Joy Vinci; Jake Edwards; Joseph Wasilewski (Biological Invasions, 2015)

Performance of the herb Verbascum thapsus along environmental gradients in its native and non‐native ranges - Tim Seipel; Jake M. Alexander; Curtis C. Daehler; Lisa J. Rew; Peter J. Edwards; Pervaiz A. Dar; Keith McDougall; Bridgett Naylor; Catherine Parks; Fredric W. Pollnac; Zafar A. Reshi; Mel Schroder; et al. (Journal of Biogeography, 2015)
Aim We evaluated whether the performance of individuals and populations of the invasive plant Verbascum thapsus differs between its native and non‐native ranges, across climate gradients, and in response to its position in a global‐scaled niche model. Location India (Kashmir) and Switzerland (native range) and Australia and USA (Hawaii, Montana and Oregon) (non‐native range). Methods We measured population characteristics (density of flowering individuals, population size), plant traits (plant height, number of flowering branches) and seed germination for 50 populations of V. thapsus growing along elevational gradients in six mountain regions around the world (two in the native range, and four in the non‐native range). We fitted linear regression models to determine the relationship of plant and population level performance variables to range, region, climate and probability of occurrence from a global niche model. Results Plant height, number of flowering branches and population density of V. thapsus did not differ consistently between the native and non‐native ranges, but the area covered by populations in the non‐native range was on average two orders of magnitude larger than the area of native populations. Within and among regions, individual plant performance traits responded variably to precipitation and mean annual temperature, depending on the climatic range of the observed populations; however, performance was greater for populations that had a greater modelled probability of occurrence. Seed germination under controlled conditions was highest between 20 and 35 °C and consistent across populations, although germination at low temperatures was substantially higher for native populations from Kashmir. Main conclusions The introduction of V. thapsus to its non‐native range is not associated with consistent increases in plant performance. Instead, plant performance is more strongly influenced by position within the climate niche of the species, position along environmental gradients, and climatic or other differences among regions. We demonstrate that individual‐level and population‐level performance traits can yield different predictors of plant performance. Therefore, future studies comparing plant performance in native and non‐native ranges should include both plant and population characteristics and should also sample the target species from multiple regions in both ranges and along environmental gradients that comprehensively represent the niche of the species.

How comparable are species distributions along elevational and latitudinal climate gradients? - Aud H. Halbritter; Jake M. Alexander; Peter J. Edwards; Regula Billeter (Global Ecology and Biogeography, 2013)
Aim Because climatic factors, especially temperature, show similar trends with elevation and latitude, it is often assumed that elevational gradients can be used as a proxy for understanding ecological processes along latitudinal gradients. We investigated the validity of this assumption for herbaceous plants, testing the hypotheses that (1) species reach the same climate limits, and (2) exhibit similar distribution patterns along both types of gradient. Location S wiss A lps and S candinavia. Methods We recorded the occurrence of 155 ruderal plant species along an elevational gradient in the Swiss Alps and a latitudinal gradient, both reaching beyond the distribution limit of most species. Principal components analysis was used to summarize climatic variation in temperature and precipitation across these gradients and assessed the relationship across species between climatic limits along the two gradients. We used logistic regressions to compare how the probability of occurrence of individual species changed with climate along the two gradients. Results We found no correlation of species principal components analysis ( PCA ) values (climate limit) along an elevational and latitudinal precipitation gradient ( PC1 ) but a positive correlation along a temperature gradient ( PC2 ). Species reached a colder climate limit (on average 244 growing degree days lower) and decreased in occurrence more gradually along the elevational compared to the latitudinal gradient. Main conclusions We suggest that the differences in distribution patterns and limits along similar climatic gradients are mainly due to the much shorter dispersal distances along elevational than latitudinal gradients, although other explanations are also possible. We can therefore expect plants in mountains and lowland regions to respond differently to rapid climate change, and so caution must be exercised when using elevation as a proxy for latitude in studies of species distribution. Nonetheless, comparative studies along such gradients can yield important insights into the factors that limit species distributions.

Genetically based differentiation in growth of multiple non-native plant species along a steep environmental gradient - Sylvia Haider; Christoph Kueffer; Peter J. Edwards; Jake M. Alexander (Oecologia, 2012)

Processes at multiple scales affect richness and similarity of non‐native plant species in mountains around the world - Tim Seipel; Christoph Kueffer; Lisa J. Rew; Curtis C. Daehler; Aníbal Pauchard; Bridgett J. Naylor; Jake M. Alexander; Peter J. Edwards; Catherine G. Parks; José Ramon Arevalo; Lohengrin A. Cavieres; Hansjörg Dietz; et al. (Global Ecology and Biogeography, 2012)
Aim To investigate how species richness and similarity of non‐native plants varies along gradients of elevation and human disturbance. Location Eight mountain regions on four continents and two oceanic islands. Methods We compared the distribution of non‐native plant species along roads in eight mountainous regions. Within each region, abundance of plant species was recorded at 41–84 sites along elevational gradients using 100‐m 2 plots located 0, 25 and 75 m from roadsides. We used mixed‐effects models to examine how local variation in species richness and similarity were affected by processes at three scales: among regions (global), along elevational gradients (regional) and with distance from the road (local). We used model selection and information criteria to choose best‐fit models of species richness along elevational gradients. We performed a hierarchical clustering of similarity to investigate human‐related factors and environmental filtering as potential drivers at the global scale. Results Species richness and similarity of non‐native plant species along elevational gradients were strongly influenced by factors operating at scales ranging from 100 m to 1000s of km. Non‐native species richness was highest in the New World regions, reflecting the effects of colonization from Europe. Similarity among regions was low and due mainly to certain Eurasian species, mostly native to temperate Europe, occurring in all New World regions. Elevation and distance from the road explained little of the variation in similarity. The elevational distribution of non‐native species richness varied, but was always greatest in the lower third of the range. In all regions, non‐native species richness declined away from roadsides. In three regions, this decline was steeper at higher elevations, and there was an interaction between distance and elevation. Main conclusions Because non‐native plant species are affected by processes operating at global, regional and local scales, a multi‐scale perspective is needed to understand their patterns of distribution. The processes involved include global dispersal, filtering along elevational gradients and differential establishment with distance from roadsides.

The role of bioclimatic origin, residence time and habitat context in shaping non-native plant distributions along an altitudinal gradient - Sylvia Haider; Jake Alexander; Hansjörg Dietz; Ludwig Trepl; Peter J. Edwards; Christoph Kueffer (Biological Invasions, 2010)

Establishment of parallel altitudinal clines in traits of native and introduced forbs - Jake M. Alexander; Peter J. Edwards; Myriam Poll; Catherine G. Parks; Hansjörg Dietz (Ecology, 2009)
Due to altered ecological and evolutionary contexts, we might expect the responses of alien plants to environmental gradients, as revealed through patterns of trait variation, to differ from those of the same species in their native range. In particular, the spread of alien plant species along such gradients might be limited by their ability to establish clinal patterns of trait variation. We investigated trends in growth and reproductive traits in natural populations of eight invasive Asteraceae forbs along altitudinal gradients in their native and introduced ranges (Valais, Switzerland, and Wallowa Mountains, Oregon, USA). Plants showed similar responses to altitude in both ranges, being generally smaller and having fewer inflorescences but larger seeds at higher altitudes. However, these trends were modified by region‐specific effects that were independent of species status (native or introduced), suggesting that any differential performance of alien species in the introduced range cannot be interpreted without a fully reciprocal approach to test the basis of these differences. Furthermore, we found differences in patterns of resource allocation to capitula among species in the native and the introduced areas. These suggest that the mechanisms underlying trait variation, for example, increasing seed size with altitude, might differ between ranges. The rapid establishment of clinal patterns of trait variation in the new range indicates that the need to respond to altitudinal gradients, possibly by local adaptation, has not limited the ability of these species to invade mountain regions. Studies are now needed to test the underlying mechanisms of altitudinal clines in traits of alien species.

Smooth muscle trans-membrane sarcoglycan complex in partial bladder outlet obstruction - Edward J. Macarak; Jake Schulz; Stephen A. Zderic; Yoshikazu Sado; Yoshifumi Ninomiya; Erzsebet Polyak; Samuel Chacko; Pamela S. Howard (Histochemistry and Cell Biology, 2006)